Intraplacental Gene Therapy with Ad-IGF-1 Corrects Naturally Occurring Rabbit Model of Intrauterine Growth Restriction - Keswani, Sundeep G. (Hum Gene Ther, 2015)
Intrauterine growth restriction (IUGR) due to placental insufficiency is a leading cause of perinatal complications for which there is no effective prenatal therapy. We have previously demonstrated that intraplacental injection of adenovirus-mediated insulin-like growth factor-1 (Ad-IGF-1) corrects fetal weight in a murine IUGR model induced by mesenteric uterine artery branch ligation. This study investigated the effect of intraplacental Ad-IGF-1 gene therapy in a rabbit model of naturally occurring IUGR (runt) due to placental insufficiency, which is similar to the human IUGR condition with onset in the early third trimester, brain sparing, and a reduction in liver weight. Laparotomy was performed on New Zealand White rabbits on day 21 of 30 days of gestation and litters were divided into five groups: Control (first position)+phosphate-buffered saline (PBS), control+Ad-IGF-1, runt (third position)+PBS, runt+Ad-IGF-1, and runt+Ad-LacZ. The effect of IGF-1 gene therapy on fetal, placental, liver, heart, lung, and musculoskeletal weights of the growth-restricted pups was examined. Protein expression after gene transfer was seen along the maternal–fetal placenta interface (n=12) 48 hr after gene therapy. There was minimal gene transfer detected in the pups or maternal organs. At term, compared with the normally grown first-position control, the runted third-position pups demonstrated significantly lower fetal, placental, liver, lung, and musculoskeletal weights. The fetal, liver, and musculoskeletal weights were restored to normal by intraplacental Ad-IGF-1 gene therapy (p<0.01), with no change in the placental weight. Intraplacental gene therapy is a novel strategy for the treatment of IUGR caused by placental insufficiency that takes advantage of an organ that will be discarded at birth. Development of nonviral IGF-1 gene delivery using placenta-specific promoters can potentially minimize toxicity to the mother and fetus and facilitate clinical translation of this novel therapy.